Marine heatwaves recurrence aggravates thermal stress in the surfgrass Phyllospadix scouleri - Vivanco-Bercovich, Manuel (2024)
The surfgrass Phyllospadix scouleri constitutes highly productive meadows along the Pacific coast of North America – a region that has been increasingly affected by severe marine heatwaves (MHWs) in recent years. Our study assessed the effects of consecutive MHWs simulated in mesocosms on critical ecophysiological descriptors of P. scouleri. Generally, our results revealed a progressive deterioration of the plant overall physiological status. Surprisingly, photosynthetic parameters only indicated physiological stress once the first heat exposure ceased (i.e., recovery period). Warming induced elevated oxidative damage and a decline in nitrate uptake rates. By contrast, non-structural carbohydrates and growth rates remained unaffected. Our results highlight the importance of including recovery periods in this sort of experiments, as they reveal delayed stress responses. Further, the accumulative detrimental effects due to the exposure to consecutive intense MHWs indicate that these events can compromise the vitality of surfgrasses and the ecosystem services provided by their meadows.